INFLUENCE OF THE CUSTOMS UNION ON ECONOMIC DEVELOPMENT OF KAZAKHSTAN. BASIC PROBLEMS AND PROSPECTS - G. G. Rahmatulina (Модернизация, инновация, развитие, 2016)
Examination of the Kazakhstan economy functioning results for the first year of the Customs Union existence proves that along with elimination of some barriers in the trade between the alliance participating countries, difficulties arose owing to disaccord in the tariff policy (particularlyrelated to railway transportation of goods), necessity to prepare new documents, etc., that negatively influence activities of Kazakhstan companies. In order to remove these difficulties, intensive mutual efforts should be taken by governmental authorities of all TC participatingcountries, opinion of respective business communities having to be compulsorily taken into account.